(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines the factors influencing the effectiveness of lessons on multimedia media, the positive impact on the activity in the lessons of the development of information and analytical competence of future teachers of technological disciplines. Based on the scientific and practical significance of the article, the summary section contains suggestions and recommendations.